Acivated Activated Carbon from Kepok Banana Peel (Musa padisiaca L.) as Methyl Orange and Methyl Violet Adsorbent in Aqueous Solution - Anindya, Bella Diska; Mahatmanti, F. Widhi; Kusumastuti, Ella; Wahyuni, Sri (Indonesian Journal of Chemical Science, 2021)
Kepok banana peel is used as raw material for activated carbon for adsorption of methyl orange and methyl violet because it has a high lignocellulose content of 90.7%. Methyl orange and methyl violet are azo dyes that have a benzene structure that is very difficult to degrade. This study aims to determine the characteristics of activated carbon from kepok banana peel waste and to determine the optimum conditions for adsorption of methyl orange and methyl by activated carbon which include pH, contact time, and initial concentration of dye. This study includes the preparation of adsorbents (activated carbon from banana peels activated ZnCl2) and adsorption optimization includes optimization of pH, contact time, and concentrations of methyl orange and methyl violet in solution. The results showed that the characterization of activated carbon using an infrared spectrophotometer contained the presence of O-H, C=O, C-H, and C-O groups on activated carbon without activation, activated ZnCl2, and after adsorption was used. Characterization using a surface area analyzer with the BET method showed that activated carbon without activation had a surface area of ​​2.278 m2/g and a pore diameter of 2.0548 nm which was included in the mesoporous category. While activated carbon activated ZnCl2 has a surface area of ​​106.287 m2/g and a pore diameter of 1.5111 nm which is included in the category of micropores. The optimum conditions for methyl orange adsorption were obtained at pH 3, a contact time of 80 minutes, and a concentration of 0.3 mmol/L, while the optimum conditions for methyl violet adsorption were obtained at pH 5, a contact time of 80 minutes, and a concentration of 0.4 mmol/L.